Middle-range scores from the patient determined disease steps scale reflect varying levels of walking dysfunction in multiple sclerosis - Robert Motl; Whitney Neal; Deborah Backus; Jeffrey Hebert; Kevin McCully; Francois Bethoux; Prudence Plummer; Alexander Ng; John Lowman; Hollie Schmidt; Robert McBurney; Gary Cutter (BMC Neurology, 2024)
Abstract Background Multiple sclerosis (MS) is a leading cause of neurological disability among young and middle-aged adults worldwide, and disability is measured using a variety of approaches, including patient reported outcome measures (PROMs) such as the Patient Determined Disease Steps (PDDS) scale. There is limited evidence for the validity of inferences from the middle-range of scores on the PDDS (i.e., 3 “gait disability” – 6 “bilateral support”), but that range of scores seemingly represents moderate disability characterized by varying levels of walking dysfunction. Purpose The current study examined whether the middle-range of scores from the PDDS reflect varying levels of walking dysfunction among people with MS. Method Participants (N = 374) completed the Patient Determined Disease Steps (PDDS) scale, Multiple Sclerosis Walking Scale-12 (MSWS-12), timed 25-foot walk (T25FW), six-minute walk (6 MW), Modified Fatigue Impact Scale (MFIS), and Multiple Sclerosis Impact Scale-29 (MSIS-29), and underwent a neurological exam for generating an Expanded Disability Status Scale (EDSS) score as part of screening and baseline data collection for a clinical trial of exercise training in MS. We undertook a series of linear trend analyses that examined differences in the outcomes of EDSS, T25FW, 6 MW, MSWS-12, MFIS subscales, and MSIS-29 subscales across the 4 levels of PDDS scores (i.e., 3–6). Results There were statistically significant and strong linear trends for EDSS (F1,370 = 306.1, p < .0001, η2 = 0.48), T25FW (F1,370 = 161.0, p < .0001, η2 = 0.32), 6 MW (F1,370 = 178.9, p < .0001, η2 = 0.34), and MSWS-12 (F1,370 = 97.0, p < .0001, η2 = 0.24). There was a strong correlation between PDDS and EDSS scores (r s = 0.695, 95% CI = 0.643, 0.748). Both PDDS and EDSS scores had strong correlations with walking outcomes, yet weaker correlations with measures of fatigue and QOL. Conclusion The PDDS could serve as a simple, inexpensive, and rapidly administered PROM for remote screening and early detection of walking dysfunction for initial eligibility into clinical trials and practice for managing mobility-specific disability in MS. Registration The study was registered on ClinicalTrials.gov on March 19, 2018 (NCT03468868).